Performance of crossbreds of Polish Merino dams with F1 rams: Finnsheep x Polish Merino. C. Preliminary results of reproductive performance of ewes - Osikowski, M.; Borys, B.; Osikowski, M. A. (Agricultural and Food Science, 1988)
The investigations were carried out on the basis of the first three reproductive cycles of ewes born in the same year. The experimental flock consisted of 100 ewes progeny of Polish Merino (PM) dams and F1 rams: Finnsheep (F) x PM; there were also 32 purebred PM used as controls. The crossbred ewes, with 25 % of F genotype, had a much better reproductive performance (117 % vs. 96 % in the PM), mainly due to a much higher prolificacy (152.2 vs. 133.6 %) and improved fertility (by 3.1 %) and the percentage of lambs weaned (higher in the crossbreds by 3.4 %).